Relaxor-Ferroelectric Films for Dielectric Tunable Applications: Effect of Film Thickness and Applied Electric Field - Minh D. Nguyen (MDPI AG, 2021)
The dielectric properties, tunability and figure-of-merit (FOM) of relaxor Pb0.9La0.1(Zr0.52Ti0.48)O3 (PLZT) films have been investigated. Dielectric measurements indicated that the dielectric constant (at zero-bias field), tunability and FOM are enhanced as the film thickness increases, which are mainly attributed to the presence of an interfacial layer near the film-electrode interface. Experimental results illustrated that a slight reduction is observed in both dielectric constant and tunability (−2%) in a wide-frequency range (10 kHz–1 MHz); meanwhile, the FOM value decreases significantly (−17%) with increasing frequency, arising from the higher dielectric loss value. The 1000-nm PLZT film shows the largest tunability of 94.6% at a maximum electric-field of 1450 kV/cm, while the highest FOM factor is 37.6 at 1000 kV/cm, due to the combination of medium tunability (88.7%) and low dielectric loss (0.0236). All these excellent results indicated that the relaxor PLZT films are promising candidates for specific applications in microwave devices.